2008
DOI: 10.1017/s0305004108001540
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert polynomials and powers of ideals

Abstract: Abstract. The growth of Hilbert coefficients for powers of ideals are studied. For a graded ideal I in the polynomial ring S = K[x1, . . . , xn] and a finitely generated graded S-module, the Hilbert coefficients ei(M/I k M ) are polynomial functions. Given two families of graded ideals (I k ) k≥0 and (J k ) k≥0 with J k ⊂ I k for all k with the property that J k J ℓ ⊂ J k+ℓ and I k I ℓ ⊂ I k+ℓ for all k and ℓ, and such that the algebras A = L k≥0 J k and B = L k≥0 I k are finitely generated, we show the functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…, x n ] are polynomial functions in k for k ≫ 0. In an explicit form this statement is given in [14]. In the same paper the question is raised whether for any ideal in a Noetherian local ring (R, m, K) a similar statement is true.…”
Section: Introductionmentioning
confidence: 96%
“…, x n ] are polynomial functions in k for k ≫ 0. In an explicit form this statement is given in [14]. In the same paper the question is raised whether for any ideal in a Noetherian local ring (R, m, K) a similar statement is true.…”
Section: Introductionmentioning
confidence: 96%
“…It is shown in Corollary 3.2 that for any finitely generated graded Smodule M , the modules Tor S i (M, I k ) are finitely graded S-modules which for k ≫ 0 have constant Krull dimension, and furthermore in Corollary 3.5 it is shown that the higher iterated Hilbert coefficients (which appear as the coefficients of the higher iterated Hilbert polynomials) are all polynomials functions. A related result has been shown in [4] for the case M/I k M and in [5] for the case Tor Observe that knowing all higher iterated Hilbert coefficients of a graded module is equivalent to knowing its h-vector, and hence the Hilbert series of the module. This is the reason why we are not only interested in the ordinary Hilbert coefficients, but in all higher iterated Hilbert coefficients.…”
Section: Introductionmentioning
confidence: 63%
“…In [4], [3], and [7] this limit is shown to exist in many special cases. In particular, in [4] it is shown to exist for graded ideals in a finitely generated standard graded algebra of depth greater than one over a field of characteristic zero.…”
Section: A Limit Superior Multiplicitymentioning
confidence: 95%